1980
DOI: 10.1001/archpedi.1980.02130170024009
|View full text |Cite
|
Sign up to set email alerts
|

Management of Acute Asthma in Childhood

Abstract: We examined the efficacy of several beta-adrenergic agents commonly used to treat asthma and evaluated the optimum route of administration. Two hundred and sixty-nine persons aged 5 to 21 years who came to the emergency ward while suffering from acute asthma were treated with either (1) inhalation isoetharine hydrochloride or (2) subcutaneous epinephrine or terbutaline sulfate. Patients were evaluated using clinical scores and pulmonary function tests and were monitored for adverse side effects. Regardless of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Our finding that serum theo¬ phylline levels were not significantly related to the outcome is in agreement with other studies, which have used the patient's or parent's reports of com¬ pliance with medication. 1,21 Others have reported that the per¬ centage of increase in peak flow after one injection of epinephrine was a sig¬ nificant predictor of the outcome of asthma attacks.316 Neither of these studies evaluated this variable using multivariable methods to control for the effects of other variables. In our study the percentage of increase in peak flow was a significant predictor of outcome when used alone but it was not significant once the predictive value of the initial peak flow was con¬ trolled for by the multivariable analy¬ sis.…”
Section: Commentmentioning
confidence: 99%
“…Our finding that serum theo¬ phylline levels were not significantly related to the outcome is in agreement with other studies, which have used the patient's or parent's reports of com¬ pliance with medication. 1,21 Others have reported that the per¬ centage of increase in peak flow after one injection of epinephrine was a sig¬ nificant predictor of the outcome of asthma attacks.316 Neither of these studies evaluated this variable using multivariable methods to control for the effects of other variables. In our study the percentage of increase in peak flow was a significant predictor of outcome when used alone but it was not significant once the predictive value of the initial peak flow was con¬ trolled for by the multivariable analy¬ sis.…”
Section: Commentmentioning
confidence: 99%